An overview of the China Bioanalytical Forum: interview with Daniel Tang. (February 2017) - Tang, Daniel
Daniel Tang talks to Sankeetha Nadarajah, Commissioning Editor ( Bioanalysis ), regarding the China Bioanalysis Forum (CBF), in which Daniel was one of the co-founders and remains as its co-chair. Daniel is currently the CEO of UP Pharma, a biologics focused bioanalytical CRO in China.